THE INFLUENCE OF ONLINE EDUCATION OVER MARKETING STUDENTS EDUCATION - STAN FLORIN ALEXANDRU; PANDURU ANDREI-DORIAN (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
This article aims on analkysing the current educational environment in the field of economics and marketing in order to determine the influence of online education over the students educational experience in hybrid or online forms of education in comparison with physical education. The context of rapid conversion of the educational institutions educational systems based on physycal attendance to an online based approach due to the pandemic of 2020 was regarded as a prime factor of the analysis that was based on case studies research, reviewing data from universities such as Netaji Subhas University and Tamaulipas Mexic University in order to obtain a global perspective of the impact of the digitalization phenomena in education. The quantitative case studies chosen offer an accurate image of the reality the university sistems had to accommodate to in order to follow the process of education as well as the downsides and limitations of educational systems based on online interaction, showcasing the affinity of students towards more traditional methods of education. The technologies used in order to establish such educational systems were discussed, from hardware limitation to software key elements that made possible for students to attend online courses during the pandemic, leading for university to increase the number of online educational programs.